Effect Size Analysis of the Use of Guided Inquiry-Based Teaching Materials on Students’ Competence - Tessa Destia Putri Lisa; Asrizal Asrizal; Festiyed Festiyed (Universitas Negeri Padang, 2023)
Teaching materials are needed in learning to deliver information systematically to students in order to achieve the expected competencies. The real condition in the field show that the use of teaching materials based on certain learning models were still limited. For this reason, this research was conducted to analyze the effect size of the use of guided inquiry-based physics and science teaching materials on students’ competence. The research method used is meta-analysis based on effect size with research subjects, namely 20 national and international articles. The results showed that the use of guided inquiry-based physics and science teaching materials was effective in increasing the competence of students at the junior high school level with a very high effect size. In addition, the use of guided inquiry-based physics and science teaching materials on teaching materials in the form of modules and textbooks gives a very high effect size and student worksheet and videos gives a high effect size. The use of guided inquiry-based physics and science teaching materials is effective in increasing the competence of students on cognitive learning outcomes with a very high effect size, on critical thinking skills, HOTS, conceptual understanding, and metacognitive abilities giving a high effect size, and on generic science skills gives a moderate effect size.